On the endogeneity of the money stock. A reply - FAND, D.I. (PSL Quarterly Review, 2014)
In this brief note, the author attempts to respond to Amadeo Gambino’s comment on the article “Some Issues in Monetary Economics” regarding the classification of the nominal money stock as an exogenous variable. JEL: E51, E40